Dental disadvantage for people with disability: a potential solution for a problematic area of care. Issue 7 (9th August 2021) - Manley, Maxwell Christopher Graham; Lane, H. L.; Doshi, M.
Abstract: This paper considers the oral health of people with disability and the disadvantage they experience compared to those who do not have a disability. There are many influencing factors for this including service provision and appropriate training for staff. A potential solution is proposed demonstrating that even advanced dental care is possible for people with complex disability. This meets the principal of equitable care for people with disability. The example concerns the provision of a lower anterior bridge for a gentleman with mid to end stage Huntington's disease and significant uncontrolled choreic movements. Intravenous conscious sedation is used to facilitate complex treatment and to demonstrate a clinical skill which can open doors for the treatment of adults with disability